Zero temperature analysis of the defect structure of B2 FeAl alloys - Bozzolo, G.; Ferrante, J.; Noebe, R.D.; Amador, C. (Scripta materialia, 1997)
The objective of this paper is to provide a consistent description of the zero-temperature defect structure of FeAl by modeling the energetics of this system using the BFS method. Several basic issues are covered, including determination of the B2 phase field, determination of the defect structure on both sides of stoichiometry, and calculation of the lattice parameter as a function of composition. Furthermore, the energetics of the BFS model provide a rationale for the limited structural stability of the B2 compound for Al-rich compositions. A good understanding of the factors influencing the atomic structure of FeAl or any other ordered system is necessary if further conclusions regarding physical and mechanical properties are to be derived from any given calculation. The calculation for FeAl seems compatible with most of the evidence gathered through the years, agreeing on the essential facts (a rationale for the observed phase field for the B2 structure, antisite substitutional defects for all compositions, decrease of the lattice parameter with increasing Fe content) and giving some indication on the probability of other defect structures.